Analysis of Southern Segment of Sumatran Fault Monitoring Bench Mark as Preliminary Approach in Updating Earthquake Hazard Map - Satrio Muhammad Alif; Arliandy Pratama (Journal of Science and Applicative Technology, 2019)
Sumatran Fault is one of hazard located in Sumatra Island. Southern segment of Sumatran fault is one of sources of earthquakes in Lampung Province. Hazard map is used as consideration in developing region. The source of hazard comes from stress accumulation of crust which can be derived from movement of points in surface. The study of points or monitoring bench mark to accommodate more precise fault movement or slip and stress accumulation is important for sustainable development in Lampung Province. Tool used for analysis is geographic information system especially buffer analysis. Available monitoring bench mark is analysed so that each bench mark can be classified based on its contribution of fault movement based on distance from segment of current fault. High class bench marks are prioritized to be used as survey sites to monitor fault movement. The other analysis is analysis to obtain region that lack bench mark to monitor segment of current fault or even discover new fault which is branch of segment of current fault. The result of this research is there are four high class bench marks. 58.54% of total segments of 164.020 km long Sumatran fault in Lampung Province is segments with no monitoring bench marks. Three most possible district to build bench mark are Airhitam, Lemong, and Ngambur District.